Squeezing force detection and signal processing for robot assisted pneumatic percussive riveting system. (September 2020) - Wang, Hua; Zhang, Jialei; Yu, Junyang
Highlights: Squeezing force based intelligent pneumatic percussive riveting process control method is proposed. End effector and force sensor mounted bucking bar for robot assisted riveting is proposed. Effective squeezing force signal processing method based on impact dynamics. The percussive riveting operation is divided into four stages. Squeezing force based real-time feedback control algorithm is proposed. Abstract: Researches in the literature treated the pneumatic percussive riveting as an open-loop process. Vibration signals of the percussive hammer and driven-head based dimensions cannot be used to real-time control each impacting of the pneumatic percussive riveting. The paper installs a force sensor on the bucking bar to collect the squeezing force signal in pneumatic percussive riveting. And a squeezing force based closed-loop process control method for robot-assisted pneumatic percussive riveting is proposed. After introducing the robot assisted pneumatic percussive riveting system, the squeezing force and the impacting frequency under different pneumatic pressure are investigated extensively with the constructed pneumatic percussive riveting platform. A squeezing force signal processing method based on time-frequency analysis is used to extract the characteristics of the percussive riveting such as the peak squeezing force, the impacting frequency and the number of impacts etc. Based on the peak squeezing force and the impacting frequency, the pneumatic percussive riveting process is divided into four stages in order to control the squeezing force of the robot riveting efficiently. A squeezing force based real-time feedback algorithm is proposed to control the squeezing force of each impacting by adjusting the pneumatic pressure and the feed force. The squeezing force based real time control method outlined in the paper is found to be effective and accurate. It can be used for robot-assisted pneumatic percussive riveting system, and closed-loop control of percussive riveting in sheet metal assembly.